Deleuze and design - Marenko, Betti; Brassett, Jamie (Deleuze connections., 2015)
"Drawing on a range of contributors, case studies and examples, this book examines ways in which we can think about design through Deleuze, and likewise how Deleuze's thought can be experimented upon and re-designed to produce new concepts. Discussions include materiality, creativity, objects, the future, innovation, the designed environment and the interaction between human non-human agents."--Back cover.